UPAYA PENINGKATAN PRESTASI BELAJAR SENI BUDAYA SISWA MATERI MUSIK POPULER DENGAN PENERAPAN METODE PEMBELAJARAN VAK (VISUALIZATION, AUDITORY, KINESTETIC) DI KELAS VIII MTSN DAIRI TAHUN PELAJAJARAN 2021/2022 - Saloko, Nurhayati (LUMBUNG AKSARA, 2022)
This research uses a type of classroom action research (CAR). The research subjects were students of Class VIII-B. In this study the researcher as the teacher (teacher), the class teacher (research partner) as the observer of the learning process of Popular Music in the form of an ensemble. The results showed that the application of Visualization, Auditory, Kinesthetic (VAK) to improve student learning outcomes in Popular Music material in the form of class VIII-B MTsN Dairi student ensembles had good success criteria. This is evidenced by an increase in learning outcomes for 27 students based on post-test scores per cycle with scores above the KKM, namely the percentage in cycle I was 63% and in cycle II 89%. The conclusions obtained from the results of this study are that the application of learning Popular Music in the form of ensembles through Visualization, Auditory, Kinestetic (VAK) can improve student learning outcomes of Class VIII-B MtsN Dairi and can make it easier for students to solve Popular Music problems in the form of ensembles. Therefore the teacher uses Visualization, Auditory, Kinesthetic (VAK) in learning Arts and Culture on Popular Music material in the form of an ensemble so that student learning outcomes increase.